Geometry of proteins: hydrogen bonding, sterics, and marginally compact tubes - Banavar, Jayanth R; Cieplak, Marek; Flammini, Alessandro; Hoang, Trinh X; Kamien, Randall D; Lezon, Timothy; Marenduzzo, Davide; Maritan, Amos; Seno, Flavio; Snir, Yehuda; Trovato, Antonio (Physical review. E, Statistical, nonlinear, and soft matter physics, 2006)
The functionality of proteins is governed by their structure in the native state. Protein structures are made up of emergent building blocks of helices and almost planar sheets. A simple coarse-grained geometrical model of a flexible tube barely subject to compaction provides a unified framework for understanding the common character of globular proteins. We argue that a recent critique of the tube idea is not well founded.